Analisis Lactat Dehydrogenase dalam Serum Darah Menggunakan Sentrifugasi - Rosnita Sebayang; Yuana Idawati; Hotman Sinaga (Jurnal Keperawatan Silampari, 2020)
This study shortens the laboratory service time by shortening the centrifuge time and obtaining serum as an examination material. The research method used was pre-experimental research. The results showed that the average LDH in the blood group centrifuged 3000 rpm 5 minutes was 309.9 U / L and 306.4 U / L centrifuged 4400 rpm 3 minutes in the blood group. In conclusion, there is no difference in serum LDH levels from blood centrifuged at 3000 rpm for 5 minutes and 4400 rpm for 3 minutes. Keywords: Centrifugation, Lactate Dehydrogenase, TAT